Fe-60-Ni-60 systematics in the eucrite parent body: A case study of Bouvante and Juvinas - Quitte, G; Latkoczy, C; Schoenbaechler, M; Halliday, A; Guenther, D (2011)
Eucrites are basaltic meteorites that cooled rapidly but are in many instances thermally metamorphosed and impact brecciated. The exact timing of these events remains unclear. In this study, Ni isotopic compositions and Fe/Ni elemental ratios are presented for two non-cumulate eucrites, Bouvante and Juvinas, including mineral separates from the latter. The samples are characterized by variable, well-resolved 60Ni-excesses consistent with the former presence of live 60Fe (t1/2=2.62Ma) at the time of eucrite crystallization. A significant fraction of Ni with a terrestrial-like composition appears to be surface correlated. This Ni may be the product of terrestrial contamination or was introduced by a chondritic impactor during brecciation. Altogether, the data provide evidence for a complex and probably multi-stage history of Fe and/or Ni redistribution, which impedes the interpretation of the chronological data. © 2011 Elsevier Ltd.